Pseudocnoside A, a new cytotoxic and antiproliferative triterpene glycoside from the sea cucumber Pseudocnus dubiosus leoninus - Careaga Quiroga, Valeria Pilar (2012)
A new triterpene glycoside, pseudocnoside A (1), was isolated from the sea cucumber Pseudocnus dubiosus leoninus. The structure of the new compound was established on the basis of extensive NMR spectroscopic analysis (1H and 13C NMR, 1H,1H-COSY, HMBC, HSQC, TOCSY and NOESY), HR-ESI-MS data and chemical transformations. In addition, the cytotoxicity and antiproliferative activities of 1 and structurally related triterpene glycosides isolated from the sea cucumbers Psolus patagonicus and Hemioedema spectabilis were evaluated against cancer cell lines A-549 and HeLa.